Enhancing performance and expressibility of complex event processing using binary tree-based directed graph - Babak Behravesh, 1977- author 204200; Siti Mariyam Shamsuddin, supervisor 289532; Hiang, Alex Sim Tze, supervisor 416711; Fakulti Kejuruteraan. Sekolah Komputeran 619086 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Doktor Falsafah (Bidang Penyelidikan: Sains Komputer))